Pineapple cultivation for small hillside farmers in St. Catherine Parish: an intervention case study - Williams, B (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The purpose of this bulletin is to describe a pineapple cultivation intervention strategy designed by the Hillside Agriculture Sub-Project (HASP) field personnel with cooperation from a farmer in St. Catherine parish. The intervention had as its goal to enhance small-farmer well-being through improved pineapple productivity, intercropping, and soil conservation measures.